Leaf water dynamics in Coffea arabica using noncontact ultrasonic intensity measurements - Jose L. Castaño-Bernal; Maria Sara Mejía; Joao L. Ealo-Cuello (Results in Engineering)
Traditional methods to evaluate physiological behaviors in leaves, such as the Scholander pressure chamber and psychrometry, provide valuable plant water status insights but often involve complex procedures or sample destruction. Air-coupled ultrasonic spectroscopy (ACUS) is an emerging non-contact technique that enables the extraction of mechanical parameters related to the relative water status in leaves, but typically requires thickness mode resonance which is unevenly achievable. This study explores the assessment of water content in Coffea arabica leaves using non-resonant ACUS transmitted intensity measurements. We demonstrate the efficacy of non-resonant and non-invasive intensity measurements to assess the vapor-water layer status of Coffea arabica leaves during dehydration processes using the Lambert-Beer law. The analysis of the interaction between transmitted intensity measurements and the leaf water content provides valuable insights into water exchange rates, stomatal activity, and poroelastic-diffusivity constant quantification. Our findings highlight the potential of using ACUS intensity measurements for evaluating leaf water dynamics and physiological responses to dehydration with a straightforward, non-destructive, and non-resonant experimental setup.